Model Reinventing Government Menuju Pemerintahan yang Baik (Good Government Governance) - Safrudin Dwi Apriyanto; Fitriaty Fitriaty; Sigit Indrawijaya (Universitas Batanghari, 2023)
New Public Management has consequences for demands for bureaucratic reform and for a higher quality of public services for the community. The spirit of creating a results-oriented government has not only surfaced in developed countries, but also in developing countries, including Indonesia. New Public Management emphasizes the bureaucracy to be more professional in managing the country. This professionalism is shown, among other things, by the quality of managing the budget, improving performance management, and using bureaucratic performance measures as a standard measure of success. This study aims to find out how to describe and analyze governance and service excellence on government performance in the Bungo District Government. The sampling technique used was a saturated sample. This study used a questionnaire as a data collection method which was given to all civil servants (PNS) Echelon II, Echelon III and or Head of OPD in the work area of the Bungo Regency Government Office, namely 178 people. The results obtained from this study include the Bungo Regency Government Governance Level in the Good category, the Bungo Regency Government service excellent level in the good category and the Bungo Regency Government Performance level in the Good category. Governance and service excellent are important factors in improving the performance of the Bungo Regency Government, where the higher the level of governance and the Service Excellent level, the more it will improve the Bungo Regency Government's performance. Service Excellent cannot be a moderating variable between the influence of Governance on improving the performance of the Bungo Regency GovernmentÂ